The elusive winter engineers: structure and materials of hazel dormouse hibernation nests. (25th November 2021) - Gubert, L.; McDonald, R. A.; Wilson, R. J.; Chanin, P.; Bennie, J. J.; Mathews, F.
Abstract: Trade‐offs between specialist use of particular resources and opportunistic use of widespread materials may present different strategies for survival. Hazel dormice Muscardinus avellanarius are arboreal mammals that in Great Britain hibernate from late autumn to mid spring in nests that are specially built at ground level. Hibernation nests are rarely encountered, and little is known about the types of construction or materials used. Specifically, it is not known whether nest materials are selected opportunistically, based on their availability, or are specialised to suit local environmental conditions. We therefore conducted a study to characterise the main materials used to construct these nests, explore the distances travelled to collect materials and investigate whether regional climate and/or local microclimate have an impact on the types of nests built. Thirty‐three hibernation nests were located through radio‐tracking, systematic searches and incidental finds. Structurally, hibernation nests were built similarly to summer nests and were most commonly constructed with an outer layer of leaves and distinct core section made of woven material. We found no correlation between nest type and the temperature recorded at nest sites. Nests were built using a mean of two materials per nest, which were both in every case available within 3m of the nest. The most frequently used materials were bracken, hazel and beech leaves, and grasses. Dormice were flexible in their use of nest materials, using various materials harvested very locally. However, dormice travelled further to collect grasses, ferns, bracken and honeysuckle, and these materials made up most of the nests in which they were found. There were also positive correlations between material abundance and usage, and suitable materials for hibernation nest construction were therefore readily available within their home range. Abstract : This study was carried out to characterise the main materials used to construct dormouse hibernation nests, explore the distances travelled to collect materials and investigate whether regional climate and/or local microclimate have an impact on the types of nests built. We found that dormice were flexible in their use of nest materials, using various materials harvested very locally. There were positive correlations between material abundance and usage, and suitable materials for hibernation nest construction were therefore readily available within their home range.